Alternative approaches in music education : case studies from the field - Clements, Ann Callistro (Rowman & Littlefield Education, 2010)
This book provides personalized case studies of music programs that are engaging in alternative approaches. The diversity of these real-world case studies will inspire questioning and curiosity, stimulate lively discussion and innovation, and provide much food for thought.